2022
DOI: 10.3390/cancers14061409
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Superparamagnetic Iron Oxide Dose Optimization in Breast Cancer Sentinel Lymph Node Identification Using a Handheld Magnetic Probe and Iron Quantitation

Abstract: This exploratory study compared doses of ferucarbotran, a superparamagnetic iron oxide nanoparticle, in sentinel lymph nodes (SLNs) and quantified the SLN iron load by dose and localization. Eighteen females aged ≥20 years scheduled for an SLN biopsy with node-negative breast cancer were divided into two equal groups and administered either 1 mL or 0.5 mL ferucarbotran. Iron content was evaluated with a handheld magnetometer and quantification device. The average iron content was 42.8 µg (range, 1.3–95.0; 0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Next, carboxydextran-coated Fe 3 O 4 MNPs with ferucarbotran (VivoTrax) has recently shown efficacy in a multicenter clinical trial on sentinel lymph nodes (SLN) biopsy involving 220 breast cancer patients where ferucarbotran exceeded the threshold identification of SLN of 94.8% [134]. An exploratory clinical study has been conducted to lower the dose of ferucarbotran, and the results showed that a 0.5 ml dose was sufficient for SLN identification [135].…”
Section: Biomedical Applications Of Fe 3 O 4 Mnpsmentioning
confidence: 99%
“…Next, carboxydextran-coated Fe 3 O 4 MNPs with ferucarbotran (VivoTrax) has recently shown efficacy in a multicenter clinical trial on sentinel lymph nodes (SLN) biopsy involving 220 breast cancer patients where ferucarbotran exceeded the threshold identification of SLN of 94.8% [134]. An exploratory clinical study has been conducted to lower the dose of ferucarbotran, and the results showed that a 0.5 ml dose was sufficient for SLN identification [135].…”
Section: Biomedical Applications Of Fe 3 O 4 Mnpsmentioning
confidence: 99%
“…Previous studies reported different injection doses (0.5 mL [ 24 , 32 ], 1.0 mL [ 21 , 31 , 34 ], 1.5 mL [ 21 , 34 ], and 2.0 mL [ 7 , 12 , 14 , 21 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 35 , 36 ] of injection volume) and injection sites (peritumoral [ 32 ], intratumoral [ 24 ], or periareolar or subareolar [ 7 , 12 , 14 , 21 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]) have noninferior detection efficiency compared with the standard method. The SLN detection rate per patient was constantly comparable to the standard method, which was also unaffected by SPIO dose [ 21 , 30 ]; a 0.5 mL volume of SPIO was sufficient for SLN identification [ 37 ]. This finding is consistent with the current subgroup analysis, nevertheless, high doses (2.0 mL of injection volume) of SPIO still reported a superior performance compared to the standard method in detecting more SLNs ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sentinel lymph node (SLN) metastasis is a crucial biomarker in breast cancer staging and treatment and the most common way to detect it is through immunohistochemical staining, as in pathobiology or nuclear medicine using radiotracers. Kindly employing the features of some commercial MNPs to accumulate in lymph nodes, [175,240,241] researchers preliminarily studied the possibilities to apply the Resovist SPIONs and MPI technique in sentinel lymph node biopsy (SLNB). [242,243] Furthermore, a customized SPION imaging probe (SPIOs@A-T) was developed for the detection of lymph node metastasis.…”
Section: Cancer Imagingmentioning
confidence: 99%